Following the model of Jesus: Rethinking women discipleship in Catholic tradition - Almirzanah, Syafa'atun (HTS teologiese studies, 2022)
In the Synoptic Gospels, women are definitely not called disciples. The term female discipleship exists only in Acts 9:36. According to the Gospel of Mark, the important aspect of discipleship is following (e.g. Mk 1:18; 2:14–15; 3:7; 5:24; 6:1; 8:34; 9:38; 10:21, 28); thus, although Mark in this case does not definitely call the women disciples, they can serve as examples of discipleship. With reference to Jesus’ approach to women, the stories in the gospel can be one of the resources, they show Jesus’ ways of looking and thinking about women. Hence to understand the mission and teaching of Jesus, is to understand the gospel. In such a way though, it is insufficient to understand it literally. In order to transcend the limit of sociological and historical context, a new understanding is needed. This article is a re-reading of the gospel and the Catholic tradition as one way to build further understanding of women and men relations, especially on the issue of women discipleship. By doing this, we can transcend ourselves beyond our socio-cultural, socio-historical even socio-psychological context. Thus, a Christian, especially, who claims to be the follower of Jesus, has more reason to be like Jesus.Contribution: An innovative exercise to develop a theological anthropology, by understanding the dynamics of human personality, and developing a theology of the women-men relationship in Catholic tradition, especially in this case re-reading the Scripture, to re-think the status of woman-man discipleship in the Catholic tradition.